KESADARAN MEREK MENINGKAT KARENA PERIKLANAN DAN HUBUNGAN MASYARAKAT (Studi Pada Konsumen Maskapai Penerbangan Citilink) - Agung Rachmadi S (Manajemen Bisnis, 2016)
In this study, researcher aims to discuss about advertising and public relations as tools to create brand awareness on Citilink Airlines. This study was a quantitative research appertaining descriptive research. Sampling technique in this study was nonprobability sampling with purposive sampling method with 100 respondents who stay in Malang Raya and respondents must be more than 17 years old and stay in Malang for long periode of time or just for awhile and know Citilink Airlines. Analyze tool of data which used was multiple regression analyze. The results of this study is advertising and public relations have significant effect on brand awareness as parsial